THE CONCEPT AND FEATURES OF LABOUR ACTIVITY OF SELF-EMPLOYED PERSONS UNDER THE LAWS OF UKRAINE - Багірова, Ганна Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to explore the legal regulation of the current domestic legislation of self-employed workers in Ukraine. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: insufficient theoretical elaboration of the problems of legal personality of self-employed persons, which is explained by the unsystematic development of law enforcement activity in the investigated sphere. Discussion: clarified that there is no single clear understanding among scientists of the relation of the category «self-employed person» with the category of «entrepreneurship», and this, in turn, is a significant shortcoming in the field of legal regulation. The issue about the concept and peculiarities of self-employed persons 'employment is quite relevant, since there is insufficient theoretical elaboration of the problems of self-employed persons' legal personality, which is explained by the unsystematic development of law-enforcement activity in the research field. In addition, there are currently no scientific papers investigating the status of self-employed persons in Ukraine in the present conditions, whereas a detailed and well-grounded analysis of the system of their rights and responsibilities is required, determining the relationship between the rights and duties of self-employed persons and other payers taxes. As a problem, in the aspect of exploring the concept and features of self-employed people's employment, it is possible to determine the lack of legal regulation of the current domestic legislation of self-employed workers in Ukraine, which needs a comprehensive, in-depth and complete study of relevant public relations in order to develop proper social relations which should aim at their effective legal regulation to address the practical issues of self-employment and people their constitutional right to work. Many eminent domestic scientists paid attention to the issue of self-employed persons' employment. A significant contribution to the study of this complex problem was made by E.M. Libanova, G.I. Kupalova and other scientists. The purpose of the article is to reveal the concept and peculiarities of self-employed people's employment in Ukraine, taking into account theoretical and practical aspects and determining the current state of scientific views on this category. The study makes the following conclusions that the main reasons for the problems in the legal regulation of self-employed persons are the obsolescence of legislative norms regarding employment of the population and labor activity, as well as a large number of areas of activity of self-employed persons. We believe that a self-employed natural person should be able to register as a self-employed person in accordance with the requirements of the current legislation of Ukraine. Summarizing the above, we can state that there is no legislative definition of the concept of «self-employed persons», its identity with the concept of «persons pursuing an independent professional activity», the absence of an exhaustive legislative list of subjects belonging to this category. Therefore, it is urgent to define a unified approach to the legislative consolidation of the concept of self-employed persons, to clearly define the circle of these persons, to streamline the relevant legal acts.